Some issues concerning behaviour modification in the schools. - Abdul Halim Othman (Universiti Kebangsaan Malaysia, 1979)
This paper highlights some of the major issues pertaining to behavior modification in the schools. Among the philosophical, conceptual and methodological issues continually raised in discussions, it appears that the philosophical ones are dominant. It has also been argued that many techniques that have been developed are indiscriminately applied to educational settings; also, these are limited in their conceptualization and it may be questioned as to their effectiveness for classroom applications. The present trend towards "behavioral humanism: is both interesting and challenging to researchers and practitioners, and it is concluded that research on "normal" children in actual situations, attempting to bring to bear more realistic approaches, would be more meaningful and relevant.